2014
DOI: 10.1007/s00192-014-2455-1
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain outcomes after transvaginal mesh revision

Abstract: Introduction and hypothesis Although the current literature discusses mesh complications including pain, as well as suggesting different techniques for removing mesh, there is little literature regarding pain outcomes after surgical removal or revision. The purpose of this study is to determine if surgical removal or revision of vaginal mesh improves patient’s subjective complaints of pelvic pain associated with original placement of mesh. Methods After obtaining approval from the Vanderbilt University Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…A study by Danford et al evaluated the post-operative pain of 233 patients who were undergoing a mesh excision for the indication of pelvic pain after a MUS. The study found that 73 % of patients reported improvement in their pain, with 18 % reporting worsening of their pain, and 19 % reporting the pelvic pain was unchanged post-operatively [41]. Hou et al found similar results in patients who presented with pelvic pain after a MUS.…”
Section: Pain and Dyspareuniamentioning
confidence: 71%
“…A study by Danford et al evaluated the post-operative pain of 233 patients who were undergoing a mesh excision for the indication of pelvic pain after a MUS. The study found that 73 % of patients reported improvement in their pain, with 18 % reporting worsening of their pain, and 19 % reporting the pelvic pain was unchanged post-operatively [41]. Hou et al found similar results in patients who presented with pelvic pain after a MUS.…”
Section: Pain and Dyspareuniamentioning
confidence: 71%
“…Additionally, women with FM are more likely to have had a hysterectomy compared with the general population, yet hysterectomy may not improve chronic pelvic pain in women with FM (Pamuk, Donmez, & Cakir, 2009; Santoro, Cronan, Adams, & Kothari, 2012; ter Borg, Gerards-Rociu, Haanen, & Westers, 1999). Similarly patients with chronic pelvic pain compared with those without recently were found to be at increased risk of not improving or even worsening after undergoing transvaginal mesh revision (Danford, Osborn, Reynolds, Biller, & Dmochowski, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies that have evaluated risk factors for needing revision surgery have kept their scope small and have not studied all possible factors. While there are published studies that report on outcomes after revision surgery for vaginal mesh complications [8][9][10][11], there are only a few studies that have focused on the indications and risk factors for needing sling revision surgery specifically [12,13]. Therefore, the primary objective of this study was to determine the indications and risk factors for needing midurethral sling revision in a large cohort of women undergoing midurethral sling placement at a tertiary care center.…”
Section: Introductionmentioning
confidence: 99%